GAMBARAN ORGANISASI RUANG PADA RUMAH LAKSMANA MAEDA DI MENTENG, JAKARTA, BERDASARKAN HOUSEHOLD ARCHAEOLOGY - Muhamad Alnoza; Desfira Ramadhania Rousthesa; Garin Dwiyanto Pharmasetiawan (Balai Arkeologi Bali, 2021)
Maeda’s house is one of colonial houses with layout and furnitures that are still remained and maintained today. Through Maeda’s house, we could still study its inhabitants social values that are reflected from their remains. This study seeks to reconstruct the social values that existed at that time, through the spatial arrangement of Maeda’s house using household archaeology. The method used in analysing this problem consists of data collection, analysis and interpretation. Based on the studies that have been carried out, it can be seen that the spatial arrangement in Maeda’s house is related to the social class of its residents. Spatial planning in this case also includes accessibility, room size and facilities. This study also provides an overview of the hierarchical figure of Maeda in managing his house, as well as showing examples of the arrangement of luxury houses in Menteng during his time. Rumah Laksamana Maeda merupakan rumah yang kaya akan sejarah dalam perjalanan Indonesia menjadi negara. Salah satu kelebihan yang dimiliki oleh Rumah Laksamana Maeda adalah tata ruang dan perabotannya yang masih terjaga hingga sekarang. Rumah Laksamana Maeda dapat dikatakan masih mencerminkan nilai sosial yang ada pada masa itu. Kajian ini berusaha untuk merekonstruksi nilai sosial yang ada pada masa itu, melalui penataan ruang rumah Maeda dengan menggunakan paradigma arkeologi rumah. Metode yang digunakan dalam menjawab masalah ini terdiri dari pengumpulan data, analisis dan interpretasi. Berdasarkan kajian yang telah dilakukan, dapat diketahui bahwa penataan ruang di rumah Maeda berkaitan dengan kelas sosial para penghuninya. Penataan ruang dalam hal ini adalah juga termasuk aksesibiltas, ukuran ruang dan fasilitas. Kajian ini juga memberikan gambaran mengenai sosok Maeda yang bersifat hirarkis dalam menata rumahnya, sekaligus juga menunjukkan contoh pola penataan rumah mewah di Menteng pada masanya.